Distance, dependence and diversity of markets: effects on market orientation - Ellis, Paul D (Journal of International Business Studies, 2007)
An inconsistent pattern of findings drawn from past research on the market orientation–performance relationship hints at the presence of extraneous sources of influence relating to geographical factors. This paper makes an initial step towards explaining these inconsistencies by advancing propositions linking market orientation with the location of the firm's marketing activities. Data from an exploratory study conducted within a small trade-dependent economy support the idea that the development of a market orientation is hindered to the extent to which a firm is dependent on diverse and distant foreign markets.